Childhood Homelessness and Adult Employment: The Role of Education, Incarceration, and Welfare Receipt - Cobb-Clark, Deborah A.; Zhu, Anna (Parkville, 2015)
This paper analyzes children’s long-term consequences of experiencing homelessness. Our primary goal is to assess the importance of the potential pathways linking childhood homelessness to adult employment. We use novel panel data that link survey and administrative data for a sample of disadvantaged adults who are homeless or at risk of homelessness. We find that those experiencing homelessness for the first time as children are less likely to be employed than those who were never homeless as a child. For women, this relationship is largely explained by the lower educational attainment and higher welfare receipt (both in general and in the form of mental illness-related disability payments) of those experiencing childhood homelessness. Higher rates of high-school incompletion and incarceration explain some of the link between childhood homelessness and men’s employment, however, childhood homelessness continues to have a substantial direct effect on male employment rates.
Melbourne Institute Working Papers
Keywords: Education and Training -- Educational level; Children; Disadvantage; Employment -- Labour force status and attachment; Income & Finance -- Poverty and disadvantage; Income & Finance -- Welfare dependence; Income, wealth and finances; Labour market; Learning, education and training; Income & Finance; Employment; Education and Training; Disadvantage; Children; Labour force status and attachment; Educational level; Poverty and disadvantage; Welfare dependence; Learning, education and training; Income, wealth and finances; Employment and unemployment